2006
DOI: 10.1002/eat.20285
|View full text |Cite
|
Sign up to set email alerts
|

Parent–adolescent relationships and the development of weight concerns from early to late adolescence

Abstract: Mothers and fathers may have unique influences on adolescent weight concerns. Intervention programming should target parent-adolescent relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
4
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 51 publications
2
50
4
2
Order By: Relevance
“…When these are not in place, problems may develop. For example, low levels of parental warmth and intimacy lead to greater weight concerns among teen girls, the onset of early dieting, and problems with dieting successfully (May et al 2006). However, 'family connectedness' seems to help, as overweight teens from such homes report fewer health compromising behaviors and less psychosocial distress (Mellin et al 2002).…”
Section: Focusing On Parent-child Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…When these are not in place, problems may develop. For example, low levels of parental warmth and intimacy lead to greater weight concerns among teen girls, the onset of early dieting, and problems with dieting successfully (May et al 2006). However, 'family connectedness' seems to help, as overweight teens from such homes report fewer health compromising behaviors and less psychosocial distress (Mellin et al 2002).…”
Section: Focusing On Parent-child Interactionsmentioning
confidence: 99%
“…It is the negative messages about weight and body shape parents convey that lead to children's disturbed eating (May et al 2006). Children are very sensitive to parents' views about their weight and physical attractiveness: at a relatively young age (9-11) they predict their parents' weight appraisals, and being seen as too fat (or too thin, for boys) is tied to lower selfesteem (Neumark-Sztainer et al 2010; Pierce and Wardle 1993).…”
Section: Focusing On Parent-child Interactionsmentioning
confidence: 99%
“…Similarly, girls, but not boys, who report greater parent-child connectedness (i.e., extent to which they perceive love from and closeness to their parents) and acceptance by their mothers and fathers appear to be less dissatisfied with their bodies concurrently (Barker and Galambos 2003) and over a period of 5 years (Boutelle et al 2009). While the mother-son relationship does not appear to affect boys' weight concerns, conflict with fathers has been associated with increased weight concerns in adolescent boys and girls (May et al 2006). The more prominent connection between parent-adolescent relationships and girls', as compared to boys', body concerns may be due to the relatively greater importance emotional support (especially from mothers) and connectedness play in the development of female adolescents (Geuzaine et al 2000).…”
Section: Parent-adolescent Relationshipmentioning
confidence: 91%
“…Short-term (i.e., 1-year follow-up) longitudinal research with early-adolescent girls indicates that parental relationships that are lower in warmth and higher in conflict are associated with less healthy dieting and a more negative body image, while more positive parental relationships are associated with a more positive body image (Archibald et al 1999). A more recent study, that followed adolescents over a period of 3 years, found that decreases in mothers' intimacy and increases in mother-daughter conflict were related to increased weight concerns among girls across the course of adolescence (May et al 2006). Similarly, girls, but not boys, who report greater parent-child connectedness (i.e., extent to which they perceive love from and closeness to their parents) and acceptance by their mothers and fathers appear to be less dissatisfied with their bodies concurrently (Barker and Galambos 2003) and over a period of 5 years (Boutelle et al 2009).…”
Section: Parent-adolescent Relationshipmentioning
confidence: 99%
“…Muitos trabalhos enfatizam que a mãe é a figura principal na dinâmica alimentar da família, cabendo a ela a seleção e a compra dos alimentos, a confecção e o fornecimento das refeições (COBELO, 2004;GOLAN;CROW, 2004;MAY et al, 2006). MAESTRO, 2002).…”
Section: Questionário De Avaliação De Consumo -Parte Aunclassified